2002
DOI: 10.1097/00002030-200204120-00018
|View full text |Cite
|
Sign up to set email alerts
|

Sexual hormones in HIV-infected patients: the influence of antiretroviral therapy

Abstract: A total of 351 determinations of sexual hormones were carried out in 189 HIV-infected men in stable clinical condition. Highly active antiretroviral therapy (HAART) was associated with increased levels of both testosterone and 17beta-estradiol, but not with luteinizing hormone (LH) and follicle-stimulating hormone (FSH). Protease inhibitors were more associated with testosterone, and non-nucleoside reverse transcriptase inhibitors with 17beta-estradiol. The values of both hormones, but not those of LH and FSH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 9 publications
2
37
2
Order By: Relevance
“…Prevalence of sexual dysfunction is widespread with most (89%) HIV positive homosexual and bisexual men reporting a decrease or loss of libido, 86% having erectile dysfunction, 68% reporting orgasmic perturbation, and 59% reporting ejaculation difficulties (Lallemand et al, 2002). Although the mechanisms of these problems are still under investigation, in large studies these side effects are particularly prevalent in those receiving a regimen containing protease inhibitors (PIs) (27.1% vs. 3.8% for untreated patients) (Collazos, Martinez, Mayo, & Ibarra, 2002;Schrooten et al, 2001;Trotta et al, 2003). The data were more striking, as a significantly larger number of PI-experienced men reported sexual problems than antiretroviral naïve patients (Schrooten et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of sexual dysfunction is widespread with most (89%) HIV positive homosexual and bisexual men reporting a decrease or loss of libido, 86% having erectile dysfunction, 68% reporting orgasmic perturbation, and 59% reporting ejaculation difficulties (Lallemand et al, 2002). Although the mechanisms of these problems are still under investigation, in large studies these side effects are particularly prevalent in those receiving a regimen containing protease inhibitors (PIs) (27.1% vs. 3.8% for untreated patients) (Collazos, Martinez, Mayo, & Ibarra, 2002;Schrooten et al, 2001;Trotta et al, 2003). The data were more striking, as a significantly larger number of PI-experienced men reported sexual problems than antiretroviral naïve patients (Schrooten et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This increase in gonadotropin levels, however, did not result in increased fT. Similarly, most [18] but not all [19] previous reports described no effect of cART on hypogonadism. The limitations of our study include the use of stored plasma samples, because they were not all taken in a morning fasting state.…”
Section: Discussionmentioning
confidence: 57%
“…But the role of estradiol in HIV sexual dysfunctions is not clear. The expected decrease in blood of the gonadotropin hormones was not confirmed (Collazos et al 2002a), and one study observed improving on sexual function despite higher blood levels of estradiol (Collazos et al 2002b). On the other side, an study on rabbits found estrogen receptors in cavernous body, and found pathophysiological changes in erectile function when rabbits are under continuous estrogen intake (Srilatha and Adaikan 2004).…”
Section: Hormonal Factorsmentioning
confidence: 99%